Practical pacifism - Fiala, Andrew, 1966- (Algora Pub., 2004)
The United States has a unique responsibility and opportunity to use democracy to end war; but, after 9/11, many can no longer imagine pacifism in any form. Practical Pacifism argues for an approach to peace that aims beyond religion toward a moral consensus that is developed ragmatically through dialogue aimed at overlapping consensus.